Extracts of Dillenia suffruticosa for medical treatments - Saiful Yazan, Latifah; Ithnin @ Mokngin, Hairuszah; Nurdin, Armania; Ismail, Maznah; Husain, Noreen; Said, Zulfahmi; Ismail, Intan Safinar; Abdul Rahman, Mohd Shukri; Harun, Mohd. Nawi (2012)
The present invention relates to methanolic and/or aqueous and/or ethyl acetate and/or dichloromethane extract of Dillenia suffruticosa for use in the treatment of solid cancer tumours, and as antimicrobial and antioxidant agents. It also relates to their preparation and dosage.